Impact of remittance on Households consumption Patterns in Vietnam - Võ, Thị Huyền Nhi (2021)
This study analyzes the impact of remittance on consumption patterns of food, education, health care, education, electricity, durable consumption, and other consumption which means to find the impact on share and level of those consumption categories in Vietnamese households from 2012 to 2016.